Refocusing the innovation process at Phillips Petroleum - Johnson, Marvin M. (Research management (Now: research technology management))
Marvin M. Johnson, in his IRI Achievement Award address, relates how Phillips evolved into a third-generation R&D organization with the link to corporate strategy in place.